Sosialisasi Pkm Manajemen Usaha Coffee Shop Menggunakan Business Model Canvas Berbasis Internet Of Things - Yulianto, Harry; Arni, Sitti; Syamsuri, Helmy (Gudang Jurnal Pengabdian Masyarakat, 2025)
The growth of coffee shop businesses in Indonesia faces significant challenges, particularly for small and medium enterprises (SMEs) that often encounter limitations in business management, marketing, and technology adoption. This community engagement initiative aims to assist the "Latimojong" coffee shop in addressing these issues through the implementation of the Business Model Canvas (BMC) integrated with Internet of Things (IoT) technology. The activities were conducted through an interactively designed socialization process, including material presentation, discussions, and mentorship. Pre-test results indicated that participants' initial understanding averaged 36%, highlighting the need for capacity building in business management. Following the socialization, the post-test scores significantly improved, averaging 87%, representing a 141.67% increase. This improvement reflects the success of the socialization program in enhancing participants' understanding. Through this initiative, the "Latimojong" coffee shop was able to formulate a more strategic and efficient business model, strengthening its competitiveness in the local market. The implementation of IoT technology and social media-based digital marketing positively impacted operational efficiency and customer experience. This Community Engagement initiative serves as a replicable model for technology-based SME empowerment, potentially supporting sustainable local economic growth.